2020
DOI: 10.1111/ajgw.12467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of delaying winter pruning of Bobal and Tempranillo grapevines on vine performance, grape and wine composition

Abstract: Background and Aims: Climate change is advancing grapevine phenology, decoupling berry technological and phenolic maturity. The aim of this study was to assess the usefulness of late winter pruning for delaying grape ripening. Methods and Results: In two Bobal and Tempranillo vineyards located in eastern Spain, vines pruned at dormancy were compared with a delayed winter pruning (late pruning) carried out just before the basal buds burst (BBCH 05). In both cultivars, late pruning delayed grape ripening, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
(104 reference statements)
0
8
0
2
Order By: Relevance
“…Moreover, “Tempranillo” is an early ripening cultivar, while “Grenache” ripens late. This may be an important factor in the adaptation of viticulture to global warming in favor of late-ripening cultivars such as “Grenache” [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, “Tempranillo” is an early ripening cultivar, while “Grenache” ripens late. This may be an important factor in the adaptation of viticulture to global warming in favor of late-ripening cultivars such as “Grenache” [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the growing season can delay phenological maturity, and affect yield components, crop coe cients, and total evapotranspiration in Vitis vinifera L. cv. 'Malbec' (Ferrara et al, 2022;Morgani et al, 2022), 'Merlot' (Allegro et al, 2020), 'Bobal' and 'Tempranillo' (Buesa et al, 2020), and Pinot Noir (Frioni et al, 2019). In contrast, Falginella et al (2022) reported that yield and qualitative parameters are not affected by different growing seasons in hot climate regions.…”
Section: Introductionmentioning
confidence: 96%
“…The cultivation of vines in new regions exposes the plants to edaphoclimatic conditions that have not yet been studied, which can cause changes in their phenology (Falginella et al, 2022;Morgani et al, 2022), and photosynthetic capacity (Ren et al, 2022), re ecting growth (Vuerich et al, 2021), yield (Gambetta et al, 2020), and fruit quality (Buesa et al, 2020;Perez-Navarro et al, 2021). Therefore, analyzing the logical behavior in different growing seasons is critical for enhancing production in new areas.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the incidence of late winter pruning in different environments, cultivars and training systems has been extensively studied: in cool-climate growing districts, this practice proved helpful in postponing budbreak, escaping late frost events, and increasing the yield (Howell and Wolpert, 1978;Friend and Trought, 2007;Friend et al, 2011). Since the postponement of the winter pruning until after budburst was shown to shift vine phenology, in warmer areas this technique was also effective in mitigating the consequences of warming due to climate change by delaying ripening and spreading grape maturity (Frioni et al, 2016;Gatti et al, 2016;Palliotti et al, 2017;Petrie et al, 2017;Moran et al, 2017;Zheng et al, 2017;Moran et al, 2018;Gatti et al, 2018;Silvestroni et al, 2018;Frioni et al, 2019;Allegro et al, 2020;Buesa et al, 2021). By contrast, the vine response to early pruning was investigated to a much lesser extent.…”
Section: Introductionmentioning
confidence: 99%